1961
DOI: 10.1103/physrev.121.569
|View full text |Cite
|
Sign up to set email alerts
|

Capture-Gamma Determination ofV51Levels

Abstract: A fast-coincidence scintillation spectrometer has been developed for thermal-neutron capture-gamma studies at the Livermore 1-Mw pool-type reactor. The added-neutron binding energy in V 51 was measured as 11.1 ±0.1 Mev. Cascade radiations for V 51 * were observed and a decay scheme is established which verifies a previously proposed (p,p') level scheme. Spin assignments for most of the V 51 (p,p f ) reported levels below 4.0 Mev are proposed and the level order for the (I/7/2) 3 proton configuration levels is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1963
1963
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Rev. 124, 1500(1961 predicted in each scheme are the same, the wave functions strongly overlap. There are several cases, however, in which Lawson's predictions are quite different from the present ones; one of these, Ti 45 , is now being measured 39 and may help to resolve the question of relative success.…”
Section: Pickup Reactions In the Ti Isotopesmentioning
confidence: 83%
“…Rev. 124, 1500(1961 predicted in each scheme are the same, the wave functions strongly overlap. There are several cases, however, in which Lawson's predictions are quite different from the present ones; one of these, Ti 45 , is now being measured 39 and may help to resolve the question of relative success.…”
Section: Pickup Reactions In the Ti Isotopesmentioning
confidence: 83%
“…The latest and most precise value for the total thermal neutron crosssection is reported by Vertebnyi et al [1] as 48+4b. Only one previous study [3] has been reported in which primary capture radiation from an enriched target was observed. Fragmentary information [2] regarding the spectrum of 7 rays following capture has been obtained from the study of radiation produced in a natural vanadium target.…”
Section: Introductionmentioning
confidence: 99%
“…The exited states of 52 V have been studied from 60's of the last century. The 52 V level scheme has mainly been performed by means of the 51 V(d, p) 52 V and 51 V(n, ) 52 V reactions [3,4,5,6,9]. The Ritz algorithm was used to construct nuclear level scheme from low energy neutron capture gamma rays.…”
Section: Introductionmentioning
confidence: 99%